Aménagement urbain et évanescence des espaces verts : bilan des parcs et jardins publics d’Abidjan - Assalé Félix Aka; Mamoutou Toure (Études Caribéennes)
The study reports on the public service offer of parks and gardens in the District of Abidjan. It is based on scientific articles, expert reports and daily newspaper accounts. The review is supplemented by the inventory of physical heritage and surveys of municipal services and users. The results show that the 124 public parks and gardens available to the District of Abidjan are organized into four main types: forest parks, neighbourhood gardens, gardens integrated into housing and the road network. But public equipment is unevenly distributed and unsatisfactory in relation to demand. The service offer is also on the decline because several parks and public gardens have disappeared or are difficult to access, while the majority of functional equipment is degraded or colonized by other activities. But public efforts do not seem to improve these public easements. The state is striving to manage part of the urban green heritage with a trend asserted by the creation of other gardens integrated into the road network that are easier to maintain, but on sites difficult to access for users. It also relies on private partners to whom another part of the heritage is rented or transferred. Here again, the public service becomes chargeable and is only accessible to part of the Abidjan population. Disparity, insufficiency, segregation, and isolation thus constitute as many obstacles which accredit the reduction of the service offer in Abidjan and perhaps a crisis of green spaces.